Re-imagining learning and teaching art: exploring embodied mark-making with foundation phase student teachers at Cape Peninsula University of Technology - Meiring, Jacoba Johanna (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.